Design Assessment of Thermal Comfort Using Computational Simulation of a Terrace House in Kuala Lumpur, Malaysia - Sadafi, Nasibeh (2008)
Terrace housing is the most common type of housing in Malaysia. They have been increasingly common in cities and towns in comparison to the detached single-family houses. However, comfort conditions in such house types vary according to the designs, modifications and adaptations of the occupants. Meanwhile, indoor environment studies in Malaysia revealed that most of the modern terrace houses are above upper thermal comfort level during day and night. The cause is simply because of unsuitable climatic design. In fact bioclimatic design considerations in terrace houses of Malaysia are not fully exploited according to occupant’s comfort needs. This study investigates the influence of different design factors in enhancing thermal condition of the house. Firstly, current condition of thermal comfort sensation for a case study terrace house in Kuala Lumpur Malaysia is investigated, using Fanger’s Predicted Mean Vote thermal comfort index. The case study was chosen in ‘Oversea Union Garden’ (OUG) area where field measurement was conducted during a three-day recording of air temperature, humidity, globe temperature and air velocity in naturally-ventilated spaces of the house. The study shows that the house is thermally comfortable for almost 15 hours during day and night, when comfort conditions mostly occurred during night hours. For improving the thermal conditions during the day, ceiling fan was used to increase the air velocity in the building. When the air temperature reaches its maximum amount, reducing the absorption of sun radiation will help more to enhance the thermal comfort condition of the house. Baseline model for the computational experiment was developed according to the results from field measurement as well as selection and adjustment of the tool. In the next step ECOTECT software has been applied for constructing the computer model of the case study terrace house. Consequently, thermal analysis part in ECOTECT has been used to assess internal thermal properties of the house in three different months of the year including: March, Jun and December. Testing of the model consists of evaluating the existing condition, testing for the shading condition and testing for the effects of including internal courtyard in the house. These evaluations revealed that suitable shading design will improve the thermal conditions, especially during noon hours when the house has the most penetration of the sun from the windows as well as highest internal temperature. Introducing the internal courtyard will increase the thermal interactions between the building and outdoor environment especially in adjacent zones. However it can improve the thermal condition by applying suitable shading design as well as suitable materials for the fabrics. According to the results of the study care should be taken for designing terrace houses in order to provide an optimal solar protection while considering the values of natural light. In courtyard buildings, the potential of courtyards to act as passive cooling can be correlated with the building composition in terms of air flow pattern.